2015
DOI: 10.1039/c5cy00891c
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic promoted coupling of carbon dioxide with epoxides: a rational investigation of the cocatalytic activity of various hydrogen bond donors

Abstract: A catalytic platform based on an onium salt used in combination with organic cocatalysts of various structures was developed for the efficient CO 2 /epoxide coupling under mild conditions. Through detailed kinetic studies by in situ FT-IR spectroscopy, a rational investigation of the efficiency of a series of commercially available hydrogen bond donors co-catalysts was realized and the influence of different parameters such as the pressure, the temperature, the catalyst loading, and the nature of the epoxide o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(63 citation statements)
references
References 59 publications
4
59
0
Order By: Relevance
“…While for the shorter ionenes it seems reasonable (based on the observed trends in reactivity) that chlorides are more closely bound to the polymer backbone and thus less readily available for the nucleophilic attack of the epoxide (compared to the bigger and more easily polarizable iodide), it seems that iodides are on the other hand more tightly attached to the polymers in those cases where longer linkers between the ammonium groups are present (thus explaining the different trend in reactivity in these cases). Finally, we tested the use of chloride-based ionenes and adding additional NaI to the reaction mixture (entries [25][26][27][28][29][30] 29,30) which is in accordance to the observations made when using the isolated salts alone (the slightly higher yields may be rationalized by some minor catalytic contribution of the excess NaI). Finally, it was also shown that addition of NaBr has more or less no positive effect (entry 31).…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…While for the shorter ionenes it seems reasonable (based on the observed trends in reactivity) that chlorides are more closely bound to the polymer backbone and thus less readily available for the nucleophilic attack of the epoxide (compared to the bigger and more easily polarizable iodide), it seems that iodides are on the other hand more tightly attached to the polymers in those cases where longer linkers between the ammonium groups are present (thus explaining the different trend in reactivity in these cases). Finally, we tested the use of chloride-based ionenes and adding additional NaI to the reaction mixture (entries [25][26][27][28][29][30] 29,30) which is in accordance to the observations made when using the isolated salts alone (the slightly higher yields may be rationalized by some minor catalytic contribution of the excess NaI). Finally, it was also shown that addition of NaBr has more or less no positive effect (entry 31).…”
Section: Resultssupporting
confidence: 65%
“…One transformation that has attracted considerable attention over the last years is the incorporation of CO 2 into epoxides to access cyclic carbonates (for selected rather recent reports with different catalyst systems please see Ref. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]). This transformation is not only interesting because of the importance of the hereby obtained dioxolanes [41,42], but it also provides a powerful approach for the utilization of CO 2 as a simple one carbon-source for organic transformations [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…The initial rate of erythritol was, however, low compared to the final conversion and TOF values observed after 23 h that are more in line with those of the other alcoholic compounds ( Table 1, . [19a] This conclusion was supported by a comparative study by Tassaing et al [23] However, in [e] k rel : ratio between the initial rate of formation of 2 a for the HBD/TBAI pair and for phenol/TBAI; the initial rates of 2 a formation were determined by in situ IR by monitoring the time evolution of the band relative to the C=O stretching of 2 a (See section S7 in the SI). By plotting the initial rates in Table 1 versus the number of hydroxyls in the HBDs ( Figure S21 in the SI), the absence of a clear correlation between catalytic activity and the number of hydroxyls in the HBDs is evident: catalysts with similar activity are found for different number of hydroxyls and HBDs with very different activity are found for the same number of hydroxyls.…”
Section: Catalytic Studiesmentioning
confidence: 74%
“…[7c] Neverthe-less, given several advantageous aspects of organocatalysis in terms of costs and sustainability, [1] the development of more active organocatalytic systems for the conversion of CO 2 to cyclic carbonates is highly sought after. [7e-g] Among them, hydroxyl HBDs are likely to represent the broadest family of catalytically active species and include functionalized monoalcohols, [20] glycols, [21] polyalcohols, [22] fluorinated alcohols, [23] hydroxy-functionalized N-heterocycles, [24] silanediols, [25] boronic acids, [26] carboxylic acids, [27] ascorbic acid [5] and several compounds containing phenolic [28] or polyhydroxyphenolic moieties. [5,19] Active HBDs for the cycloaddition of CO 2 to epoxides include several classes of compounds that have been careful reviewed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation